(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes various methods of assessing the gender characteristics of participants in socio-political processes in English-speaking countries and Russia through the prism of media discourse. The changes in the content approach to this assessment in retrospect are considered, and both explicit and hidden ways of expressing it are revealed.